Respuesta :
F = {(0, 1), (2, 4), (4, 6), (6, 8)}
G = {(2, 5), (4, 7), (5, 8), (6, 9), (7, 5)}
F(6) = 8
G(6) = 9
so
(F - G) (6) = 8 - 9 = -1
G = {(2, 5), (4, 7), (5, 8), (6, 9), (7, 5)}
F(6) = 8
G(6) = 9
so
(F - G) (6) = 8 - 9 = -1
Answer:
The value of (F-G)(6) is -1.
Step-by-step explanation:
The given functions are defined as
[tex]F = \{(0, 1), (2, 4), (4, 6), (6, 8)\}[/tex]
[tex]G = \{(2, 5), (4, 7), (5, 8), (6, 9), (7, 5)\}[/tex]
We need to find the value of (F-G)(6).
Using subtraction of two function property, we get
[tex](F-G)(6)=F(6)-G(6)[/tex] .... (1)
From the given functions it is cleared that the value of function F is 8 at x=6 and the value of function G is 9 at x=6. It means
[tex]F(6)=8[/tex]
[tex]G(6)=9[/tex]
Substitute F(6)=8 and G(6)=9 in equation (1).
[tex](F-G)(6)=8-9[/tex]
[tex](F-G)(6)=-1[/tex]
Therefore the value of (F-G)(6) is -1.